Correlates of aggression in personality disorders: an update - Mancke, Falk; Herpertz, Sabine; Bertsch, Katja (Current psychiatry reports, 2018)
Purpose of ReviewThis review article aims at giving an update on studies investigating correlates of aggression in personality disorders during the last 5 years.Recent FindingsMost data refer to borderline personality disorder (BPD) and antisocial personality disorder (ASPD). In BPD, emotion dysregulation, hypersensitivity to interpersonal rejection/threat, increased rumination, increased negative urgency, aggression-related knowledge structures, and invalidation were either corroborated or emerged as psychological correlates of aggression, while reduced ambiguity sensitivity, hyposensitivity to interpersonal threat, and reduced mindfulness were associated with aggression in ASPD. Neurobiologically, alterations of the monoaminooxidase-A-, the oxytocinergic-, and the prefrontal-limbic-system as well as increases of the thyroid hormone T3, γ-aminobutyric acid and several inflammatory markers were associated with increased aggression across various personality disorders.SummaryOur understanding of correlates of aggression in personality disorders has increased over the last 5 years. More efforts in improving the conceptualization of personality disorders and aggression are needed to develop innovative treatments for those affected.
Gesehen am 10.10.2019